Pouchitis After Immune Checkpoint Inhibitors - Gabriel Sperling; Yinghong Wang (Annals of Internal Medicine: Clinical Cases)
Immune checkpoint inhibitors (ICIs) are becoming increasingly used for various cancers, but their association with immune-related adverse events often leads to significant morbidity and mortality. Here we report 2 unusual cases of pouchitis after ICI therapy—treated with steroids and biologics. To our knowledge, this is the first example to be reported in literature. One patient achieved short-term remission, while the other achieved long-term remission without further flares.